Estimation method of minimum preventive maintenance interval for avionics system - Mahayudin, Aisyah Razana (2014)
Maintenance simulation is important to foresee the impact on the availability percentage and maintenance cost before actual maintenance is done. Therefore, it is important to simulate a maintenance activity as close as possible to real life. The maintenance simulation requires a preset preventive maintenance interval (PMI). The thesis analyzes simulation for many PMIs at various maintenance types which are perfect, imperfect and minimal maintenance. Since the most realistic maintenance simulation is the main focus, imperfect maintenance is the best routine to simulate the maintenance activity. However, previous data of the maintenance activity are needed in order to simulate imperfect maintenance. Thus, in the thesis also proposes a way to simulate imperfect maintenance without having previous data of the maintenance activity. In order to prove the simulation procedure, the same maintenance activity is simulated with different types of maintenance degree which are perfect maintenance and minimal maintenance. Then, the simulation of imperfect maintenance is then compared with simulations of perfect and minimal maintenance. The simulation methodologies used are Monte Carlo simulation and Discrete Event simulation. For a case study of the simulation, two subsystems of avionics system are used. The subsystems are Flight Instruments and Engine Indication System. The avionics systems used is from Cirrus SR20 with Perspective Avionics. From the simulation, perfect maintenance has the highest availability percentage and minimal maintenance always has the lowest availability percentage. Meanwhile imperfect maintenance’s availability percentage are in between perfect and imperfect maintenance. As for maintenance cost, minimal maintenance has the highest maintenance cost and perfect maintenance has the lowest maintenance cost. Meanwhile imperfect maintenance has a maintenance cost in between perfect and minimal maintenance. Based on these findings, it can be concluded that the methodology to simulate imperfect maintenance is relevant. Then, the relationship between maintenance cost and availability percentage is discussed for each maintenance type. From the discussion, the minimum PMI is proposed based on preset criteria.